Taʿlīm al-Mufradāt li al-Nāṭiqīn bi-Ghayr al-Lughah al-ʿArabiyyah: Naẓariyyan wa Taṭbīqiyyan - Fakhrurasih Fakhrurasih (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2014)
Vocabulary is one of the fundamental components of language, playing a vital role in both spoken and written communication. It is also an essential linguistic element that language learners must acquire and master in order to achieve the desired level of language proficiency. Teaching vocabulary to non-native speakers of Arabic constitutes a core aspect of Arabic language instruction because, without adequate vocabulary acquisition, learners cannot attain the expected communicative competence and will encounter considerable difficulties in language use. Therefore, substantial attention should be devoted to teaching Arabic vocabulary to non-native speakers from both theoretical and practical perspectives, enabling learners to develop the linguistic competence necessary for effective communication.